Optimizing The Use Of Digital Libraries In Strengthening Educational Infrastructure In The Era Of Information Disruption - Naku, Robertus Kristianto; Kurniawati, Dewi (Mahir : Jurnal Ilmu Pendidikan dan Pembelajaran, 2023)
Optimizing the using of digital-based libraries (digital libraries) is a major transformation in the world of education today. Digital libraries offer many conveniences and diverse connectivity. This research aims to analyze opportunities for using digital libraries in the era of information disruption. The research results show that in the era of information disruption, the use of digital-based libraries is very helpful, especially in supporting learning activities. Digital libraries are easy to access, portable, economical, rich in references, equipped with searching tools, keywords and knowledge sharing. This research uses a qualitative approach.